Nematodes of amphibians from Java, Indonesia, with a description of new species, Meteterakis wonosoboensis n. sp. (Nematoda : Heterakoidea) - Purwaningsih, Endang; Dewi, Kartika; Hasegawa, Hideo (Zootaxa, 2015)
During a survey on the parasites of amphibians of Indonesia, toads (30 Bufo melanostictus) and 246 frogs (213 Fejervarya cancrivora, 11 F. limnocharis, 22 Rana macrodon from West Java and 68 F. cancrivora from Central Java) were examined for parasitic nematodes. Three species of nematodes were found and described, i.e. Meteterakis wonosoboensis n. sp. from Fejervaria cancrivora; Meteterakis japonica from Bufo melanostictus, F. cancrivora and F. limnocharis; and Chabaudus sp. from F. cancrivora, F. limnocharis and Rana macrodon. Meteterakis wonosoboensis n. sp. is distinguished from other species of the genus by the length and shape of spicules, the number of caudal papillae, the presence of gubernaculum in male and the presence of vulval flap in female. Bufo melanostictus and Java are recorded as new host and locality for M. japonica, respectively.